Reproductive biology of the introduced sailfin catfish Pterygoplichthys pardalis (Pisces: Loricariidae) in peninsular Malaysia - Samat, Abdullah; Md. Yusoff, Fatimah; Arshad, Aziz; Ghaffar, M. A.; Nor, S. M.; Magalhaes, André L. B.; Das, Simon Kumar (Indian Council of Agricultural Research, 2016)
Reproductive biology of the introduced sailfin cat fish Pterygoplichthys pardalis in the Langat River of peninsular Malaysia was studied. Fish samples were collected monthly from Langat River during March 2003-June 2004. The sex ratio observed for P. pardalis was female-biased with 1: 2. Gonadal maturity stage is achieved at 12.5 cm standard length (SL) for males and 13.0 cm SL for females. This species appeared to have continuous spawning that peaked when water levels were high between September and January. Egg sizes were found to reach as large as 3.3 mm in dia in the ovary; suggesting that they spawn in batches. Fecundity varied from 1297 to 18791 numbers per brood, proportional to individual size. Data obtained from this study indicate that the introduced sailfin cat fish has successfully colonised in Langat River in Malaysia.